Acceptance, obedience and resistance: Children's perceptions of street trading in Nigeria. (9th July 2021) - Osaiyuwu, Abiodun; Burch, Sarah; Sandu, Adriana
Abstract: Street trading is an under‐researched form of child labour. This study explores experiences of children aged 10–15 in Nigeria, using interviews and focus groups. Children largely accepted the need to contribute economically to the family, as well as their own school expenses. Trading was demanding, and there were hidden costs, such as reduced school attendance, but an emphasis on obedience made challenge difficult. Children felt resistance, but knowledge of their rights did not support acting on these feelings. Accounts demonstrated the difficulties of living at the intersection of competing constructions of childhood.